Simple method for estimating snow strength using CPT sleeve friction data - McCallum, A B; Wiegand, A (Journal of Cold Regions Engineering, 2018)
The in situ strength of polar snow is not easily measured; most assessments rely on indices derived from snow density and/or are limited in depth. To overcome these deficiencies, modified cone penetration testing (CPT) equipment is used to obtain rate-variable tip-resistance and sleeve-friction data in Antarctic firn to depths of 10 m. A physical model of snow deformation ahead of the penetrating cone is considered to allow generation of a continuous profile of snow strength. Dynamic profiling of strength to depth in polar snow is possible using the cone penetration test. However, more in situ strength data are needed to comprehensively validate the simple method presented herein.